Cytology and sexuality of 11 species of Elatostema (Urticaceae) in limestone karsts suggests that apomixis is a recurring phenomenon. (1st March 2017) - Fu, Long‐Fei; Su, Lan‐Ying; Mallik, Azim; Wen, Fang; Wei, Yi‐Gang
Abstract : Limestone karsts across southern China to southeastern Asia are renowned biodiversity hotspots. The karst are characterized by exposed calcareous rocks, seasonal droughts and thin soils that are deficient in N and P but with high Ca and Mg content. The stressful habitat may result in high biodiversity through mechanisms such as niche differentiation, hybridization, polyploidy and apomixis. The genus Elatostema (Urticaceae) has particularily high species diversity in this area and can be used a model genus to explore the mechanisms of speciation. We conducted cytological studies on 11 species of Elatostema from 12 populations in Guangxi, China. We found five populations to be diploid (2n = 26), and seven triploid populations (2n = 39). We infer x = 13 as the basic chromosome number of Elatostema . The chromosome numbers 2n = 26 and 2n = 39 were both found in populations of E. longistipulum, indicating that this species comprise both diploids and triploids. Both male and female plants of Elatostema were found to be diploid. In contrast, the triploids found were all female plants, and these produce seeds, presumably by apomixis. We found no clear relationship between ploidy level or reproductive pathway and endemism in Elatostema which might be because Elatostema species are wind‐pollinated and independent of biotic pollinators. However, a random sample of 11 karst species revealed that ca 2/3 appeared to be apomictic, suggesting that it is a widespread reproductive strategy of Elatostema in the limestone karsts of Guangxi. Apomixis enables plants to reproduce and disperse from a single individual, allowing 'hopeful monsters' adapted to a new habitat to form stable populations.